Development and analysis of a clean methane production system. (1st June 2022) - Bolt, Andre; Dincer, Ibrahim; Agelin-Chaab, Martin
Highlights: The proposed multigeneration system produces 5 useful outputs. The proposed system synthesizes CH4, from H2 and CO2 produced renewably. The overall energy and exergy efficiency during heating mode is 61% and 28.64%. Abstract: In the presented study, the design for a new renewable integrated multigeneration system that is capable of producing natural gas as well as methane is proposed. The multigeneration system harnesses solar energy through the implementation of a solar power tower and receives its electrical energy input by harnessing wind energy from horizontal axis wind turbines. The designed system is capable of storing the thermal energy collected from the solar tower through the integration of a molten salt storage sub-system containing a hot and cold storage tank. The methane produced from the system is renewably synthesized. This is essentially achieved from the syngas generated through the combustion of biomass, and the H2 gas that was produced from the electrical input from wind energy to a polymer electrolyte membrane system. The system is expected to perform at its best from May to July, due to the greatest wind velocity, hours of daylight, and solar radiation available during these months. Additionally, the useful outputs produced from the system consist of electrical power, heat for space heating, cooling and domestic hot water. During normal operating conditions, the system has an overall energy and exergy efficiency of 61% and 28.64%, respectively during its heating mode. Additionally, the system has an energetic and exergetic COP of 0.546 and 0.135 during the heating mode and an energetic and exergetic COP of 4.661 and 0.4934 during the cooling mode. Moreover, numerous parametric studies are performed to identify how the system operates during different operating conditions.